Integrated circuits packages & applications (Minnesota : Video Training Resource [production company] : Virginia : Coastal Skills Training [distributor], 1987)
Explain how hybrid integrated circuits are constrycted and used, identify all types of integrated circuits by their packaging and detail all the major applications of integrated circuits
Keywords: Integrated circuits -- Design and construction; Hybrid integrated circuits